Combination of Plasma Rich in Growth Factors With Topical 4% Hydroquinone Compared With Topical 4% Hydroquinone Alone in the Treatment of Dermal Type of Melasma: A Single-Blinded Randomized Split-Face Study - Rezvan Amiri; Mahbooba Karimi Maskooni; Alireza Farsinejad; Mehran Karvar; Maryam Khalili; Mahin Aflatoonian (Wolters Kluwer Medknow Publications, 2024)
Background: Response to the current available treatments of melasma, dermal type, in particular, is usually gradual and can result in possible side effects. Aim and Objectives: In this study, we aim to evaluate the efficacy of the combination of plasma rich in growth factors (PRGF) and topical 4% hydroquinone (HQ) in comparison with monotherapy using topical 4% HQ alone in the treatment of dermal type of melasma. Materials and Methods: This is a single-blinded, randomized, split-face clinical trial on twenty female patients with dermal type of melasma. Patients were asked to apply topical 4% HQ on both sides of their face at night for 6 months. In each participant, one side of the face was randomly chosen to receive monthly intradermal injections of PRGF for 3 sessions. Efficacy of the treatment was assessed using hemi melasma area and severity index (MASI) score, physician's global assessment (PGA), and patients' global assessment (PtGA). Results: Both groups revealed significant improvement in hemi-MASI score during the treatment course. Mean percentage of improvement at the end of study was 40.38 ± 6.04% and 33.42 ± 3.23% in the combination therapy and monotherapy groups, respectively (P = 0.31). PGA demonstrated excellent-to-marked improvement in melasma in 25% and 5% of patients in the combination therapy and monotherapy groups, respectively (P = 0.31). PtGA showed high levels of satisfaction in 15% of patients in the combination therapy group (vs. 0% in the monotherapy group) (P = 0.05). Conclusion: Differences between the two treatment groups in terms of hemi-MASI and PGA scores were not statistically significant; however, patients demonstrated higher satisfaction with combination of PRGF and topical 4% HQ compared with topical HQ alone. Thereby, combination of PRGF and topical 4% HQ can be suggested as a safe alternative therapeutic approach and may hold promise in the development of future therapeutic options for dermal type of melasma.